Solidariedade e conflito: Estado liberal e nação católica no Pará sob o pastorado de Dom Macedo Costa (1862-1889) - Neves, Fernando Arthur de Freitas (2009)
It wanted church to separate up itself of the state? It wanted the state to break up itself of church? Impossible to recognize in the hierarchy a positive answer for this quandary when if it perceives the gale of mobilized forces to church to remain in the head of the souls and institutions to its constant work of religious regeneration and of the necessary structures to the apport of resources for offering of symbolic services and the civil services given by this. If some clergymen in Brazil, for example of other national states had assumed the responsibility to slash a statal apparatus according to liberal models of England, U.S.A. and France, neither therefore must attribute to church or the hierarchy to the predilection for this type of state. In the decade of 1870, the prelates romanizadores of Pará and Pernambuco, D. Macedo Costa and D. Vital Lima, respectively, had been condemned to the arrest for do not suspend the injunction determinate to the Carmo Third Order , according to determination of the emperor, crime against the authority of this about the religious subjects, until then of court of appeals of the civil power. This conviction is the apex of the litigation between state and church in Brazil of the last quarter of century XIX, therefore from this moment the alliances of this block of power will suffer other crises ( for example, the civil processions and wax candles, civil cemeteries, civil marriages and civil registers), gaining more powerness ,and leading to the separation of the two institutions in 1890, by the decree of the recent republic. This has been the way covered for the historiography when investigating the relations between state and church. Notedly, the historians of church have designated the condition of secondary of church before the state, now that one does not control none of the necessary material ways to its institucional reproduction. To this respect, this work looks up to demonstrate the cases as of the bishoprics, in the born of the republic that were completely unprovided of the necessary resources to the continuity of the proposal catholic being essential to recover the constructions, such as churches, chapels, convents and high schools, therefore thanks to these church had obtained, to make present in the hearts and minds of the faithful. Thus being, the mote of the research is try to perceive the relation between church in the Amazônia, state and the national episcopate during pastorate of Dom the Macedo Costa